OncomiR or antioncomiR: Role of miRNAs in Acute Myeloid Leukemia. Issue 2 (28th January 2019) - He, Chengcheng; Luo, Bo; Jiang, Nan; Liang, Yu; He, Yancheng; Zeng, Jingyuan; Liu, Jiajia; Zheng, Xiaoli
Abstract: Acute Myeloid Leukemia (AML) is a hematopoietic progenitor/stem cell disorder in which neoplastic myeloblasts are stopped at an immature stage of differentiation and lost the normal ability of proliferation and apoptosis. MicroRNAs (miRNAs) are small noncoding, single-stranded RNA molecules that can mediate the expression of target genes. While miRNAs mean to contribute the developments of normal functions, abnormal expression of miRNAs and regulations on their corresponding targets have often been found in the developments of AML and described in recent years. In leukemia, miRNAs may function as regulatory molecules, acting as oncogenes or tumor suppressors. Overexpression of miRNAs can down-regulate tumor suppressors or other genes involved in cell differentiation, thereby contributing to AML formation. Similarly, miRNAs can down-regulate different proteins with oncogenic activity as tumor suppressors. We herein review the current data on miRNAs, specifically their targets and their biological function based on apoptosis in the development of AML.